The Relationship Between The Duration Of Zumba Exercise And Total Cholesterol Levels - Tasrif Ahmad (Journal of Medical Laboratory in Infectious and Degenerative Diseases, 2024)
Zumba exercise is included in sports that can reduce fat deposits, this is because the energy source needed in exercise apart from burning carbohydrates in the form of glucose is also from burning fat reserves or triglycerides. Stored triglycerides will be converted into fatty acids and glycerol. Glycerol will enter the body's metabolism to be converted into glucose and pyruvic acid. Fatty acids will be broken down together with carbohydrates and oxygen to become energy (ATP) in the mitochondria. Therefore, Zumba exercise is a sport that can reduce cholesterol levels and waist circumference ratio,The aim of this study was to determine the relationship between the duration of Zumba exercise and total cholesterol levels. This research is a type of observational analytical research using a purposive sampling technique with 28 samples obtained from HERCULES FITNES Karanganyar. Measurements of total cholesterol levels were obtained from respondents who filled out a questionnaire and fasted for 8 - 12 hours before taking samples, then the blood samples were taken to the Clinical Laboratory of the National College of Health Sciences to check total cholesterol levels using the Clima MC 15 Photometer. Research results In all samples, cholesterol levels were found to have a value that exceeded the normal limit, namely 205 mg/dl. The conclusion of research conducted on 28 respondents who took part in Zumba exercise at HERCULES FITNES using the Spearman correlation test showed that there was a significant correlation with a P-value of 0.776, meaning that there was a relationship between the duration of Zumba exercise and total cholesterol levels